An EGCG-mediated self-assembled micellar complex acts as a bioactive drug carrier. (30th August 2023) - Liu, Chao; Wu, Hao; Duan, Hongxia; Hou, Yan; Wang, Shuangqing; Liu, Yanhong; Zhang, Xintong; Zhao, Heming; Gong, Liming; Wan, Hongshuang; Zeng, Bowen; Quan, Xiuquan; et al.
Graphical abstract: Highlights: EGCG was transformed from a bioactive ingredient to a bioactive drug carrier. The lipid solubility, stability, and bioactivity of EGCG were improved. The tough issue of targeted delivery of water-soluble EGCG was improved. Co-loading and delivering of EGCG and PTX were achieved without inert carrier. This strategy exhibited a synergistic effect in the treatment of breast tumors. Abstract: Epigallocatechin gallate (EGCG) has attracted the increasing attention of many researchers, especially in the field of tumor therapy. However, EGCG has poor fat solubility, low stability, low bioavailability, and a high effective dose in vivo. Traditional drug delivery methods are difficult to deliver the water-soluble EGCG efficiently and in high doses to tumor sites. To address these issues, a new type of strategy has been tried in this study to transform EGCG from a "Bioactive natural ingredient" into a "Bioactive drug carrier". Briefly, the EGCG was modified with a fat-soluble 9-fluorene methoxy carbonyl (Fmoc) motif, and the obtained EGCG-Fmoc showed a considerable improvement in lipid solubility and stability. Interestingly, EGCG-Fmoc obtained the characteristic of self-assembly in water, making it easier to take up by tumor cells. Furthermore, the self-assembled nanocomplex exhibited paclitaxel encapsulation performance and could achieve the dual delivery of EGCG and paclitaxel.